2010
DOI: 10.1074/mcp.m900479-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Export Marks the Early Phase of Gametocytogenesis of the Human Malaria Parasite Plasmodium falciparum

Abstract: Despite over a century of study of malaria parasites, parts of the Plasmodium falciparum life cycle remain virtually unknown. One of these is the early gametocyte stage, a round shaped cell morphologically similar to an asexual trophozoite in which major cellular transformations ensure subsequent development of the elongated gametocyte. We developed a protocol to obtain for the first time highly purified preparations of early gametocytes using a transgenic line expressing a green fluorescent protein from the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
321
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(337 citation statements)
references
References 46 publications
15
321
0
1
Order By: Relevance
“…SSP3 was not detected in lysates of mixed blood stages (see Fig. S4E in the supplemental material), which is in agreement with the lack of SSP3 in the previously published proteomes of asexual and sexual blood stages of P. falciparum and P. berghei (29)(30)(31)(32)(33). Because SSP3 contains 13 conserved cysteine residues, we tested whether these residues form disulfide bonds by analyzing the electrophoretic mobility of SSP3 under reducing and nonreducing (omitting the disulfide-reducing agent BME and with no boiling) conditions.…”
Section: Ssp3 Is a Predicted Type I Transmembrane Proteinsupporting
confidence: 77%
See 1 more Smart Citation
“…SSP3 was not detected in lysates of mixed blood stages (see Fig. S4E in the supplemental material), which is in agreement with the lack of SSP3 in the previously published proteomes of asexual and sexual blood stages of P. falciparum and P. berghei (29)(30)(31)(32)(33). Because SSP3 contains 13 conserved cysteine residues, we tested whether these residues form disulfide bonds by analyzing the electrophoretic mobility of SSP3 under reducing and nonreducing (omitting the disulfide-reducing agent BME and with no boiling) conditions.…”
Section: Ssp3 Is a Predicted Type I Transmembrane Proteinsupporting
confidence: 77%
“…It is also possible that the lack of SSP3 on the sporozoite surface might alter the distribution or functionality of other proteins important for attachment and/or gliding in vitro. It has been shown that TRAP and S6, another TRAP family protein, are necessary for initial adhesion to glass slides (33). TRAP proteins are released from micronemes onto the sporozoite surface and are redistributed from the front to the back of the sporozoite.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,45,46 The rise in the knob density in mature asexual stages results in the increased number of vertical constraints between the spectrin network and the lipid bilayer, which further stiffens the membrane. 47 In GIEs, KAHRP and PfEMP1 are not expressed 48,49 and STEVORs may perform an analogous role by increasing vertical constraints between the cytoskeleton and the lipid bilayer. Protein-protein interactions essential for the erythrocyte membrane mechanical properties are modulated by posttranscriptional modifications of either cytoskeleton or parasite proteins.…”
Section: Discussionmentioning
confidence: 99%
“…0.5 ml was then separated from the ookinete culture and incubated with Hoechst 33342/PBS and imaged as above. Red blood cells in the remainder of the ookinete culture were lysed in a 140 mM NH 4 Cl solution on ice, ookinetes were collected by centrifugation and processed further for Western blotting with Roche monoclonal anti-GFP antibody (#11814460001).…”
Section: Live Microscopy and Western Blotting Of Blood Stage P Berghmentioning
confidence: 99%
“…Thus, many predicted sexual stage proteins remain uncharacterized and have unknown functions; specifically, of the 2430 proteins identified by mass-spectrometry in P. falciparum gametocytes (stages I-II, IV and V) [3,4], 830 (34%) are annotated with "unknown function" (www.plasmodb.org; June 5, 2014). Their molecular and cellular descriptions are vital to prioritize candidate surface proteins for transmission-blocking vaccine approaches that interfere with parasite development or inhibit infection of the mosquito vector by the ookinete [5].…”
Section: Introductionmentioning
confidence: 99%